Flexible identities and cross-border knowledge networking. Issue 4 (3rd October 2016) - Moore, Fiona
Abstract : Purpose: This paper aims to explore and discuss the use of the flexible, discursive nature of ethnic identity as a means of facilitating the construction and use of transnational knowledge networks. Design/methodology/approach: This paper examines the influence of "intangibles" on international business (IB), using a case study examining how Taiwanese people in London construct and use their professional networks for knowledge management. The methodology is ethnographic, including participant-observation, interviews and archival research. Findings: Taiwanese businesspeople in London used their ethnic identity for networking, not only within the Taiwanese community, but also combined different identities to network through different groups. The findings suggest that the flexible nature of identity provides a means by which knowledge networks can be constructed across borders, providing insight into the actual processes through which knowledge is transferred in IB. Research limitations/implications: An identity approach can add a more nuanced analysis of real-life situations to the more traditional culture-focused approach. Greater methodological variety is needed if IB studies are to incorporate more complex perspectives on cross-cultural management, and to develop this study's conclusions. Practical implications: Managers who are aware of the complexities of ethnic identity can exploit these among themselves and their employees to seek out new sources of knowledge. Originality/value: This paper provides insight into the means and processes through which transnational networks are constructed and knowledge shared across borders, and the seldom-analysed role of identity, in this case ethnic identity, in these phenomena.